Penerapan Prinsip Transparansi, Partisipatif, dan Akuntabilitas dalam Pengadaan Barang dan Jasa di Kabupaten Sidenreng Rappang - Jamaluddin Ahmad (JIA: Jurnal Ilmiah Administrasi, 2012)
Applying transparency, participatory, and accountability in the proccess of supplying products and services is needed to make a good governance. Local government of Sidenreng Rappang has committed to apply those principles thoughout government's policy, and so this is actually an important research subject. This research type is a descriptive-qualitative using several methods to collect data, to mention documentating, questioning or interview, and a role of informant (source). Then those data will be analyzed using descriptive-qualitative analysis. The result shows us that the need of transparency, participatory, and accountability principles has been optimally applied. And it has been proven by a deputy observer of society who has helped apply those three principles. The main role lies in the human resources and the enforcement of sanctions within government's regulations or procedures.